Running activity profile of adolescent tennis players during match play - Sperlich, B.; Hoppe, M. W.; Baumgart, C.; Bornefeld, J.; Freiwald, J.; Holmberg, H. C. (Pediatric Exercise Science, 2014)
The aims of this study were (1) to assess the running activities of adolescent tennis players during match play with respect to velocity, acceleration, and deceleration; (2) to characterize changes in these activities during the course of a match; and (3) to identify potential differences between winners and losers. Twenty well-trained adolescent male athletes (13 ± 1 y) played one simulated match each (giving a total of 10 matches), during which distances covered at different velocity categories (0 to < 1, 1 to < 2, 2 to < 3, 3 to < 4, and >= 4 m·s-1) and number of running activities involving high velocity ( >= 3 m·s-1), acceleration ( >= 2 m·s-2), and deceleration ( <= -2 m·s-2) were monitored using a global positioning system (10 Hz). Heart rate was also assessed. The total match time, total distance covered, peak velocity, and mean heart rate were 81.2 ± 14.6 min, 3362 ± 869 m, 4.4 ± 0.8 m·s-1, and 159 ± 12 beats·min-1, respectively. Running activities involving high acceleration (0.6 ± 0.2 n·min-1) or deceleration (0.6 ± 0.2 n·min-1) were three times as frequent as those involving high veloc- ity (0.2 ± 0.1 n·min-1). No change in the pattern of running activities (P >= .13, d <= 0.39) and no differences between winners and losers (P >= .22, d <= 0.53) were evident during match play. We conclude that training of well-trained adolescent male tennis players need not focus on further development of their running abilities, since this physical component of multifactorial tennis performance does not change during the course of a match and does not differ between the winners and losers.